Pembentukan Akhlak dalam Perspektif al-Uṣūl at-Tarbiyah al-Islāmiyyah: Solusi atas Dekadensi Moral Remaja: Studi deskriptif di MA NU Nahdlatul Fata Petekeyan - Hilmi, Iklil Nafis; Laila, Azzah Nor (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study discusses the increasingly alarming issue of moral decadence among adolescents, triggered by technological developments and a lack of strong moral guidance in Islamic educational institutions. The purpose of this study is to describe the concept of moral formation from the perspective of al-Uṣūl al-Islāmiyyah by Ahmad Fu'ad al-Ahwānī and its implementation at MA NU Nahdlatul Fata Petekeyan. The method used is a descriptive approach. -Tarbiyah al-Islāmiyyah by Ahmad Fu'ad al-Ahwānī and its implementation at MA NU Nahdlatul Fata Petekeyan. The method used is a qualitative descriptive approach, supported by a quantitative survey, to obtain an empirical picture of the application of Islamic educational values in shaping student character. Al-Ahwānī's theory emphasizes the three main pillars of Islamic education, namely tauhid, akhlak, and amal as a unity that shapes pious individuals. The results of this study show that these values are instilled through the formation of habits, teacher role models, and religious activities in madrasas, which foster students' spiritual, moral, and social awareness. The conclusion of this study confirms that the concept of al-Uṣūl at-Tarbiyah al-Islāmiyyah is relevant and can be applied as a solution to the decline in youth morals, as it helps create a balance between faith, knowledge, and deeds in the Islamic education system.